Predicting verdicts using pre-trial attitudes and standard of proof - Lundrigan, Samantha (Legal and criminological psychology, 2016)
Purpose. Several measures have been developed of juror pre-trial attitudes and interpretations of beyond reasonable doubt (BRD). These have been primarily tested in North American samples. We aimed to integrate the literature on these two issues, and explored whether the effect of jurors' pre-trial attitudes on verdicts is mediated by their interpretations of BRD. We also aimed to establish the relative predictive utility of the various measures and their relevance to a non–North American sample. Methods. A total of 113 members of the jury-eligible British public completed three measures of juror pre-trial attitudes (i.e., Revised Legal Attitudes Questionnaire-23 [RLAQ-23], Juror Bias Scale [JBS], and Pre-trial Juror Attitudes Questionnaire [PJAQ]) and two measures of BRD (i.e., direct rating [DR] and membership function [MF] methods). Participants also rendered a verdict on a hypothetical burglary case. Results. With the exception of the RLAQ-23, the pre-trial attitude measures and the two measures of BRD were significantly independent predictors of verdicts. The PJAQ outperformed the RLAQ-23 and JBS, whereas the MF method outperformed the DR method. We found support for a partial mediation model predicting verdicts, whereby interpretations of BRD (measured by the MF method) partially mediated the effect of pre-trial juror attitudes (measured by the PJAQ) on verdicts. Conclusions.mThese findings underscore the importance of examining both juror pre-trial attitudes and interpretations of BRD when studying juror decision making.